A Numerical Model of Vapour Transfer and Phase Change in Unsaturated Freezing Soils - Sihao Liang; Jidong Teng; Feng Shan; Sheng Zhang (Advances in Civil Engineering)
In recent studies, vapour transfer is reported to lead to remarkable frost heave in unsaturated soils, but how to better model this process has not been answered. In order to avoid the great uncertainty caused by the phase change term of vapour-water-ice in the numerical iteration process, a new numerical model is developed based on the coupled thermal and hydrological processes. The new model avoids using the local equilibrium assumption and the hydraulic relations that accounts for liquid water flow, which provides a new way for the water-heat coupling movement problem. The model is established by using COMSOL Multiphysics, which is a multiphysics simulation software through finite element analysis. The model is evaluated by comparing simulated results with data from column freezing experiments for unsaturated coarse-grained soils. Simulated values of the total water content compare well with experimental values. The model is proved to be applicable and numerically stable for a high-speed railway subgrade involving simultaneous heat and moisture transport. An agreement can be found between the predicted and measured frost/thawed depth and soil moisture profiles, demonstrating that the model is able to simulate rapidly changing boundary conditions and nonlinear water content profiles in the soil.